If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 7 = 2n + -6 Reorder the terms: 7 + n = 2n + -6 Reorder the terms: 7 + n = -6 + 2n Solving 7 + n = -6 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 7 + n + -2n = -6 + 2n + -2n Combine like terms: n + -2n = -1n 7 + -1n = -6 + 2n + -2n Combine like terms: 2n + -2n = 0 7 + -1n = -6 + 0 7 + -1n = -6 Add '-7' to each side of the equation. 7 + -7 + -1n = -6 + -7 Combine like terms: 7 + -7 = 0 0 + -1n = -6 + -7 -1n = -6 + -7 Combine like terms: -6 + -7 = -13 -1n = -13 Divide each side by '-1'. n = 13 Simplifying n = 13
| 5(8x+6)+12=402 | | 5(5+8r)= | | 2a=a+13 | | 2a=s+13 | | -142=-2-10x | | 3-(3-7)=43 | | 5-7y=h+7 | | x+30+x+20+x+10=180 | | 10(3+11g)= | | -3-7(3+2m)=-94 | | -0.6=0.3(k+2) | | 2x+4y+7-2z= | | 3m-2n=7m-7-4.8n | | 2x-10+2x=3(4x-6)+6 | | 2a=a+16 | | 7(5b+4)= | | 2X-3/15 | | m^2-28m=11 | | 2v-68=v | | E=7+5x | | 6+2x+9=24+32+6x+12 | | -7(10-10x)-8x= | | (3x+4)+(2x+2)=5(1x-1)+8 | | 2p-26=p | | 4(x-3)+18=3(x+3) | | 2x-3(x-5)=7 | | 6b-61=b+4 | | 6(3n-7)=84 | | 2x^4/5=25 | | x(x+2)=x(5+x) | | 10a+4(a+1)=32 | | 7(6+7a)= |